2016
DOI: 10.5271/sjweh.3600
|View full text |Cite
|
Sign up to set email alerts
|

Sickness absence and permanent work disability in relation to upper- and lower-body pain and occupational mechanical and psychosocial exposures

Abstract: Combined pain in the upper and lower body was associated with sickness absence and permanent work disability, and high occupational mechanical exposures further increased the risk. Job strain showed a modest association with sickness absence, while low social support at work was associated with both outcomes, especially permanent work disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
3
18
0
2
Order By: Relevance
“…Despite the possibility of over-adjustment, the risk estimates for disability pension were generally increased among the exposed compared with the non-exposed (ie, no exposure years), A somewhat similar methodological challenge was presented in a recent study by Sommer et al (20) showing that high occupational mechanical exposure per se (assessed by upper-and lower-body JEM) were associated with two-fold risk of sickness absence and a similar, but insignificant increase in the risk of permanent work disability (ie, disability pension and flexible job subsidies). They explained their statistically non-significant results on disability pension by low statistical power: during 104 weeks of follow-up, 119 participants (0.5%) were registered with transition to permanent work disability.…”
Section: Interpretation Of Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Despite the possibility of over-adjustment, the risk estimates for disability pension were generally increased among the exposed compared with the non-exposed (ie, no exposure years), A somewhat similar methodological challenge was presented in a recent study by Sommer et al (20) showing that high occupational mechanical exposure per se (assessed by upper-and lower-body JEM) were associated with two-fold risk of sickness absence and a similar, but insignificant increase in the risk of permanent work disability (ie, disability pension and flexible job subsidies). They explained their statistically non-significant results on disability pension by low statistical power: during 104 weeks of follow-up, 119 participants (0.5%) were registered with transition to permanent work disability.…”
Section: Interpretation Of Resultsmentioning
confidence: 93%
“…Specifically, factors such as heavy lifting and kneeling work have previously been related to sickness absence (6-9). To our knowledge, only one study has investigated the association between occupational mechanical exposure assessed by a JEM and labor market outcomes (20). That study observed an increased risk of LTSA among individuals with high mechanical exposure in their latest job function compared to those with low mechanical exposure.…”
Section: Interpretation Of Resultsmentioning
confidence: 93%
See 3 more Smart Citations